PRODUCTION OF PROTEASE ENZYME FROM BACTERIA IN HOT SPRING OF SOUTH SULAWESI, Bacillus licheniformis HSA3-1a - Hasnah Natsir; Irwan R (Hasanuddin University, 2015)
Bacillus licheniformis HSA3-1a is able to produce extracellular protease. The aim of this research was to find out its production optimum time, consentration of MnCl2, temperature and optimum pH, also the cofactor influence on activity protease from B. licheniformis HSA3-1a. The protease activity was tested with a modified method of Walter. Protease production time was optimum for 36 hours with an activity value of 0,394 U/mL, protein content was 132,35 mg/mL. The Optimum condition of protease enzyme were pH 7,0 and temperature 45 ⁰C with an activity value of 0,0463 U/mL. Protease activity could be inhibited by MnCl2 concentration of 0,01 - 0,03 M.